Does Religious Identity Moderate Economic Voting? Evidence from Indonesia - Budi, Arya (Muslim Politics Review, 2024)
Scholars have long suggested that economic voting is contingent on political factors, but how social identity contributes to such contingent economic voting has been overlooked. While the literature suggests the presence of direct function of religion on voting decisions, we are not sure about religion’s other functions. By treating religion as a social identity, this article seeks to uncover a moderating function of religion on economic voting. It draws on an embedded exit poll survey in Indonesian gubernatorial and mayoral elections in 2020, covering 9,400 respondents. This paper finds that the self-identification of religious identity moderates economic perception in the voting decision. Although the findings show strong evidence of economic voting, they challenge previous studies arguing that religion is a weak predictor in a new democracy with a Muslim-majority population. This paper contributes to the literature on economic voting and the role of religion in the voting decision.